Loan Ratios, Information Asymmetry and Fragility among Banks in Kenya - Bwire, Albert C. (African Journal of Education,Science and Technology (AJEST), 2016)
The goal of the research was to establish the mediating role of information asymmetry on loan ratios and fragility among commercial banks in Kenya. The study utilized explanatory research design. The population was forty-two commercial banks, however following exclusions number declined to thirty. Evidence highlights loan ratios have predictive abilities in identifying fragility among commercial banks in Kenya. Log total assets (logta) partially mediates the relationship between loan ratios and bank fragility. Information asymmetry therefore has a role in bank fragility. The study brings to the fore matters’ worth of future study. That the log of total assets partially mediates the relationship between loan ratios and fragility among commercial banks in Kenya. Size has implications on information disclosure by banks. The ability to predict fragility has socio-economic benefits to the country and other bank stakeholders. This research mainstreams the role of information asymmetry in bank fragility studies with bank’s asset side of the balance sheet as the focus